The co-colonization prevalence of Pseudomonas aeruginosa and Aspergillus fumigatus in cystic fibrosis: A systematic review and meta-analysis. (December 2018) - Zhao, Jingming; Cheng, Wei; He, Xigang; Liu, Yanli
Abstract: Purpose: The co-colonization prevalence of P. aeruginosa and A. fumigatus in cystic fibrosis (CF) has been inconsistently reported. The purpose of this systematic review and meta-analysis was to estimate the overall co-colonization prevalence of P. aeruginosa and A. fumigatus in CF. Methods: The Embase, PubMed and Web of Science databases were systematically searched for studies reporting the co-colonization prevalence of P. aeruginosa and A. fumigatus in CF. The co-colonization prevalence of two pathogenic microorganisms in the individual studies was assessed by calculating the proportion and 95% confidence interval (CI). The random effects model was used to calculate the pooled prevalence. The I 2 test was used to assess statistical heterogeneity. The funnel plot and two statistical methods were used to assess publication bias. Results: Twenty-three eligible studies were included in this analysis. The pooled co-colonization prevalence of P. aeruginosa and A. fumigatus in CF patients was 15.8% (95% CI: 9.9–21.8). The co-colonization prevalence of P. aeruginosa and A. fumigatus chronic colonization was lower than that of intermittent colonization, higher in sputum cultures than in bronchoalveolar lavage (BAL) cultures, and lower in children than in adults. There was a statistically significant difference in co-colonization prevalence among studies from different decades, but the prevalence was similar in different geographical regions and with different study types. Conclusions: The co-colonization prevalence of P. aeruginosa and A. fumigatus in the lower respiratory tract of CF patients was high. The anti-infective treatment in exacerbation of CF should be considered to cover the two pathogenic microorganisms simultaneously. Large-scale research is still needed to obtain more accurate co-colonization data. Highlights: The co-colonization prevalence of P. aeruginosa and A. fumigatus in CF was high. The pooled co-colonization prevalence of P. aeruginosa and A. fumigatus in CF was 15.8%. The co-colonization was associated with the worsening of CF.